2021
DOI: 10.1007/s00586-021-06877-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating how combined multifidus injury and facet joint compression influence changes in surrounding muscles and facet degeneration in the rat

Abstract: Purpose To examine whether unilateral multifidus damage could promote degeneration at the L5-6 facet joint (FJ) and compensatory changes in lumbo-pelvic muscles in rats. Methods 12 facet clamp, 12 facet sham and 7 control rats were studied. Facet clamp and sham animals had the left L5-6 FJ exposed, and the clamp group had a mild compressive clamp applied using hemostatic forceps to model post-traumatic arthritis. Both groups then had the left multifidus detached from the L1-L6 spinous processes. Animals were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We have also observed significant changes in echotextural variables of quadriceps femoris muscles in the sham-operated group and in some pectoral-brachial region muscles of both sham-operated and surgery animals. Klahsen et al 30 have recently observed that facet degeneration and neuromyopathic changes can also occur, to a previously unrecognized extent, in sham-operated rats; that would explain the occurrence of echotextural changes in some quadriceps femoris muscles of sham-operated animals. 30 Considering the echotextural changes in the non-neurosegmentally linked brachial myotome, we speculate that these alterations can be attributed to shifting the center of gravity of operated animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also observed significant changes in echotextural variables of quadriceps femoris muscles in the sham-operated group and in some pectoral-brachial region muscles of both sham-operated and surgery animals. Klahsen et al 30 have recently observed that facet degeneration and neuromyopathic changes can also occur, to a previously unrecognized extent, in sham-operated rats; that would explain the occurrence of echotextural changes in some quadriceps femoris muscles of sham-operated animals. 30 Considering the echotextural changes in the non-neurosegmentally linked brachial myotome, we speculate that these alterations can be attributed to shifting the center of gravity of operated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Klahsen et al 30 have recently observed that facet degeneration and neuromyopathic changes can also occur, to a previously unrecognized extent, in sham-operated rats; that would explain the occurrence of echotextural changes in some quadriceps femoris muscles of sham-operated animals. 30 Considering the echotextural changes in the non-neurosegmentally linked brachial myotome, we speculate that these alterations can be attributed to shifting the center of gravity of operated animals. It has been shown that the neonatal spinal transected rats develop autonomous weight-supported stepping as adults; the hind limbs of these rats bore significantly less weight than intact rats’ hind limbs (37% body weight on hindlimbs, 63% on forelimbs) 31 .…”
Section: Discussionmentioning
confidence: 99%